2021
DOI: 10.1038/s41598-020-80393-z
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Apgar score is strongly associated with postoperative ICU admission

Abstract: Immediate postoperative intensive care unit (ICU) admission can increase the survival rate in patients undergoing high-risk surgeries. Nevertheless, less than 15% of such patients are immediately admitted to the ICU due to no reliable criteria for admission. The surgical Apgar score (SAS) (0–10) can be used to predict postoperative complications, mortality rates, and ICU admission after high-risk intra-abdominal surgery. Our study was performed to determine the relationship between the SAS and postoperative IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Such unmeasured variables may explain the finding that the male gender was independently associated with higher odds of ICU transfer from the ward, although this finding is reported in multiple prior studies without a clear explanation. [15][16][17] Institutional practice patterns may have influenced the decision for ICU transfer from the ward, and some complications such as atrial fibrillation may have been managed on the ward in other institutions. Additionally, despite the present evidence suggesting that pancreatectomy type (proximal vs. distal) is not independently associated with postoperative ICU-related outcomes, an analysis of a larger multi-institutional cohort focusing independently on these two populations may have yielded different results.…”
Section: Discussionmentioning
confidence: 99%
“…Such unmeasured variables may explain the finding that the male gender was independently associated with higher odds of ICU transfer from the ward, although this finding is reported in multiple prior studies without a clear explanation. [15][16][17] Institutional practice patterns may have influenced the decision for ICU transfer from the ward, and some complications such as atrial fibrillation may have been managed on the ward in other institutions. Additionally, despite the present evidence suggesting that pancreatectomy type (proximal vs. distal) is not independently associated with postoperative ICU-related outcomes, an analysis of a larger multi-institutional cohort focusing independently on these two populations may have yielded different results.…”
Section: Discussionmentioning
confidence: 99%
“…SAS has been tested in various surgeries with satisfactory results. Calculation of SAS is simple, and it does not require biochemical workups, acute or chronic disease category, clinical assessment, or depend on the nature of the surgery (elective, urgent, emergency) (13). Therefore, SAS is a simple and useful triage tool for anesthesiologist, surgeons and intensivists.…”
Section: Question 1 Which Kind Of Cancer Patients May Benefit From Postoperative Intensive Care Monitoring?mentioning
confidence: 99%
“…A score built from those three parameters has proved to be a strong predictor of postoperative outcomes of the patient and due to its availability, inexpensively collectable data and low reliance on technological capacity and resource of the health care centre it is a simple and powerful tool, for assessing risk of post-operative outcomes [5,6]. Since its introduction capability of surgical apgar score in predicting post operative outcomes after different kinds of surgeries and even in predicting outcomes after ICU admissions has been correlated, most of the studies found surgical apgar score to be a strong predictor of the outcomes [7,2,8,9,10].…”
Section: Introductionmentioning
confidence: 99%